Digital Transformation to Improve Teachers' Learning Management and Students' Science Life Skills - Nurdin, D.; Marnita, M.; Ghani, M. F. B. A. (Jurnal Pendidikan IPA Indonesia, 2023)
This study aims to describe the quality of teachers’ learning management based on digital transformation and improving students’ science life skills. Paradigm change shifts in the context of learning based on textbooks to switching to learning accompanied by digital technology that has forced better teacher competence so that they can surf well in class. The sample in this study was 270 eighth-grade students in junior high and eight science study field teachers on the concept of the human circulatory system. This research used a mixed method with a sequential exploratory design, combining qualitative and quantitative data analysis. The study results show that digital transformation strategies can create teachers’ learning management that is fun, meaningful, full of creativity, and effective in terms of time and cost. The findings in this study are (1) Digital transformation is one of the teachers’ strategies to create better quality, fun, meaningful, creative, and effective learning management in class; (2) The implementation of digital transformation-based teachers’ learning management can explore students’ science life skills on the circulatory system. This research concludes that the application of digital transformation can improve the quality of teachers’ learning management and students’ science life skills in the Bireuen District.